Dieta, área de uso e transporte de girinos de Ameerega trivittata (Spix, 1824) (Anura: Dendrobatidae) em uma região de floresta de terra firme na Amazônia Oriental - (:unkn) unknown (Museu Paraense Emilio Goeldi, 2012)
This study explores aspects of diet, use area and transport tadpoles Ameerega trivittata on an upland forest region in eastern Amazonia. We collected 56 specimens in total (48 males and eight females), and of these 44 individuals of A. trivittata had checked their stomach contents where ants subfamily Myrmicinae was the taxon most consumed by males, and Isoptera by females. This is probably due to the need for acquisition of alkaloids by males present in ants, which gives them a high degree of toxicity, and hence protection, since it is the males that perform parental care in this species, carrying tadpoles to pools . We estimate the use of area of ​​four males, which are on average twice higher than that found for the same species in the Peruvian Amazon. There was no relationship between the size of males and abundance and / or average size of the loaded tadpoles and there was no relationship between the area of ​​pools and plenty of tadpoles, but there was a decrease in the abundance of tadpoles in relation to the abundance of Odonata nymphs, which corroborates other work for dendrobatids, as these are known to regulate the populations of tadpoles.
Keywords: Anfíbio; Dendrobatídeos; Girino; Dieta; Juruti - PA; Amazônia Brasileira; Alimentação; Flushing; Abundância; Poças; Odonata; CNPQ::CIENCIAS BIOLOGICAS::ZOOLOGIA::COMPORTAMENTO ANIMAL